Impact of psychological contracts on organizational trust and commitment of nurses in Ghaem hospital - Mashhad province - A Kafashpour; S Mortazavi; S Pour (Tehran University of Medical Sciences, 2013)
Background: Organizational commitment among nurses as care providers provided the quality of patient care by their conservation. Therefore, nurses are committed to the investment and the competitive advantage of clinics and hospitals which have a significant impact on increasing the quality of services. In this study, the effect of psychological contracts and organizational trust studiedas an organizational commitment of Ghaem hospital nurses in Mashhad province.Materials and methods: Strategy survey - analysis of data obtained for the study of 193 Ghaem hospital nurses in the city of Mashhad through distributed questionnaires by the structural equations and partial the least squares method to seek the help of software were analyzed.Results: The results indicated that the first, model of the material used has a strong theoretical model that is to predict nurses' organizational commitment. Secondly, all direct and indirect relationships between variables in the model were significant. But the relationship between organizational trust and nurses' continuous commitment was not confirmed.Conclusion: This study indicates not only depends on nurses' organizational commitment to creating positive psychological space, but also they are in the reliability of this space gives rise to the obligation. On the other hand, the quality of the organizational commitment for nurses could be effective and efficient in use of available resources. Therefore, hospital administrators need to be more attention to an effective component of organizational commitment as supply facilities, participate in decision making, good communication, and job enrichment.